Thermoplastic polyolefin material and preparation method thereof
By using modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist and inorganic flame retardant in thermoplastic polyolefin materials, the problem that TPO materials are prone to cracking after adding flame retardant is solved, and high flame retardant, crack resistance and drip resistance are improved.
Patent Information
- Application Number
- CN202411992847.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Existing thermoplastic polyolefin (TPO) materials are prone to cracking after adding a large amount of flame retardant, resulting in limited flame retardant properties and applications.
By adding modified polyhedral oligosilsesquioxane and its derivative flame retardant synergist to the thermoplastic polyolefin material, combined with inorganic flame retardant, a carbon layer, a ceramic barrier layer and a glass-like protective film are formed to enhance the flame retardant properties and crack resistance of the material.
It significantly improves the flame retardant and cracking resistance of thermoplastic polyolefin materials, prevents dripping, and reduces the amount of flame retardant, and improves the overall performance of the material.
Smart Images

Figure CN119752021A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of materials, and in particular to a thermoplastic polyolefin material. Background Art
[0002] Polyhedral oligomericsilsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0003] Thermoplastic polyolefin (TPO) materials have low density and great bending properties. They have excellent weather resistance and can resist erosion from harsh environmental factors such as ultraviolet rays, high temperature, and low temperature, maintaining long-term stability and performance. Currently, TPO materials are widely used in shoe materials, pipes, tires, membrane materials, and cable materials. However, TPO materials have no chemical cross-linking structure and are mainly composed of polymer chain entanglement points and physical cross-linking structures. When a large amount of flame retardants are added, the entanglement between molecules becomes weaker, so it is easier to cause TPO to crack. This is a common problem of highly flame-retardant TPO, which limits the application of TPO in China. Therefore, it is very necessary to develop a highly flame-retardant, crack-resistant, and drip-proof halogen-free TPO material. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the present invention proposes a thermoplastic polyolefin material, aiming to solve the problem of poor flame retardancy of the current TPO material.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a thermoplastic polyolefin material, wherein the raw materials of the thermoplastic polyolefin material, measured in parts by weight, include:
[0007] EVA 20-30 parts,
[0008] POE15-22 parts,
[0009] PE20-30 parts,
[0010] 90-130 parts of inorganic flame retardant,
[0011] 3-8 parts of compatibilizer,
[0012] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0013] Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0014]
[0015] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0016] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0017] In some embodiments of the present invention, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group;
[0018] And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
[0019] In some embodiments of the present invention, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0020]
[0021] In some embodiments of the present invention, the molar ratio of compound 1 to compound 2 is 2:1.
[0022] In some embodiments of the present invention, the method for preparing the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps:
[0023] Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist;
[0024] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0025] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0026] In some embodiments of the present invention, the raw materials of the thermoplastic polyolefin material include, by weight:
[0027] EVA 20-30 parts,
[0028] POE15-22 parts,
[0029] PE20-30 parts,
[0030] 90-120 parts of inorganic flame retardant,
[0031] 3-8 parts of compatibilizer,
[0032] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
[0033] In some embodiments of the present invention, the inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide, and calcium carbonate.
[0034] In some embodiments of the present invention, the raw material of the thermoplastic polyolefin material also includes at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, the raw materials are calculated by weight, the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.
[0035] The second aspect of the present invention provides a method for preparing the above-mentioned thermoplastic polyolefin material, comprising the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder to obtain granular material, namely the thermoplastic polyolefin material.
[0036] In some embodiments of the present invention, the raw material further includes at least one of a lubricant, an antioxidant, and a light stabilizer.
[0037] The thermoplastic polyolefin material of the invention comprises EVA, POE, PE, a compatibilizer, an inorganic flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the inorganic flame retardant to synergistically flame retardant, thereby reducing the amount of the flame retardant and improving the flame retardant and crack resistance of the thermoplastic polyolefin material. The thermoplastic polyolefin material provided by the present invention has excellent flame retardant and crack resistance, and can prevent dripping during the combustion process. The modified POSS and its derivatives flame retardant synergist is in the form of a colorless viscous liquid, which has little effect on the performance of the thermoplastic polyolefin material when added to the thermoplastic polyolefin material, and does not require a very high addition amount to obtain a thermoplastic polyolefin material with excellent flame retardancy. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The molecular structure diagram of the modified POSS flame retardant synergist 1 of the present invention;
[0039] Figure 2 This is a molecular structure diagram of the modified POSS flame retardant synergist 2 of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0041] Unless defined otherwise, all technical and scientific terms used herein have the common meaning in the art to which the claimed subject matter belongs.
[0042] EVA: Ethylene-vinyl acetate copolymer is a foam material with both rubber and plastic properties. It is made of ethylene and vinyl acetate copolymers and is non-toxic, harmless and environmentally friendly. It has good resistance to low temperatures, ozone and mildew, and has rubber-like elasticity and high transparency. In addition, EVA material also has good shock resistance, cushioning, moisture resistance and sound insulation, can keep warm and cold, and is resistant to chemical corrosion.
[0043] POE: Polyolefin elastomer is a thermoplastic elastomer that is achieved by in-situ polymerization of ethylene and octene using a metallocene catalyst. It has excellent toughness, processability, weather resistance, heat aging resistance and UV resistance. Its molecular structure gives it a narrow relative molecular mass distribution and uniform short chain branching distribution, thus having excellent physical and mechanical properties (such as high elasticity, high strength, high elongation) and good low temperature performance.
[0044] PE: Polyethylene is a thermoplastic resin made from the polymerization of ethylene monomers, with excellent low temperature resistance and chemical stability. PE materials are widely used in various fields, including packaging, containers, pipes, wires and cables, etc. PE materials are often used in food packaging, cling film, water pipes, bubble bags, etc. due to their excellent chemical stability and wide applicability.
[0045] EMA: ethylene-methyl acrylate copolymer, ethylene-methyl acrylate copolymer, is made by copolymerization of ethylene, methyl acrylate and auxiliary monomers. EMA has the characteristics of transparency, low density and elasticity, and also exhibits excellent waterproof performance, chemical stability, heat resistance and insulation performance. This material has a very wide range of applications, mainly in food packaging, pharmaceutical packaging, electronic and electrical equipment, construction and automotive parts.
[0046] Polyhedral oligomericsilsesquioxane (POSS) is a special organic amorphous material. It is a polycyclic organic monomer composed of a silicon framework and its embedded oxygen atoms. It is an inorganic-organic hybrid nanomaterial. The inorganic silicon cage core in POSS decomposes under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior, thereby delaying further decomposition of the material. POSS shows great application potential in the field of flame retardants.
[0047] Thermoplastic polyolefin (TPO) materials have low density and great bending properties. They have excellent weather resistance and can resist erosion from harsh environmental factors such as ultraviolet rays, high temperature, and low temperature, maintaining long-term stability and performance. Currently, TPO materials are widely used in shoe materials, pipes, tires, membrane materials, and cable materials. However, TPO materials have no chemical cross-linking structure and are mainly composed of polymer chain entanglement points and physical cross-linking structures. When a large amount of flame retardants are added, the entanglement between molecules becomes weaker, so it is easier to cause TPO to crack. This is a common problem of highly flame-retardant TPO, which limits the application of TPO in China. Therefore, it is very necessary to develop a highly flame-retardant, crack-resistant, and drip-proof halogen-free TPO material.
[0048] In order to solve the above problems, the first aspect of the present invention provides a thermoplastic polyolefin material. The raw materials of the thermoplastic polyolefin material, measured by weight, include:
[0049] EVA 20-30 parts,
[0050] POE15-22 parts,
[0051] PE20-30 parts,
[0052] 90-130 parts of inorganic flame retardant,
[0053] 3-8 parts of compatibilizer,
[0054] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist,
[0055] The structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is:
[0056]
[0057] Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene;
[0058] R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
[0059] It can be understood that when R1 connected to Si in the inorganic silicon cage core is a phenylene group, since the phenylene group contains a benzene ring, the carbon-to-hydrogen ratio and the carbon content of the benzene ring are relatively high. When burned, it works together with the large amount of Si contained in the inorganic silicon cage core to further improve the flame retardant properties of the inorganic silicon cage core, thereby improving the flame retardant properties of the modified polyhedral oligomeric silsesquioxane flame retardant synergist.
[0060] The thermoplastic polyolefin material of the invention comprises EVA, POE, PE, a compatibilizer, an inorganic flame retardant and a flame retardant synergist of modified polyhedral oligomeric silsesquioxane and its derivatives. Since the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist contains boron, a ring structure R2 with a carbon-to-hydrogen ratio greater than 1, and two inorganic silicon cage cores, the boron element forms boric acid during the combustion process, and the boric acid dehydrates and carbonizes the surface of the material to form a carbon layer; the two inorganic silicon cage cores decompose under heat to form a dense ceramic barrier layer, which isolates the release of combustible gas and the entry of external heat into the interior; the ring structure R2 with a carbon-to-hydrogen ratio greater than 1 has a higher carbon-to-hydrogen ratio, and the benzofuran group and the polycyclic aromatic group contain a large amount of carbon elements. A large amount of carbon elements will form a glassy protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air, prevent the transfer of heat, and reduce the release of combustible gases. These structures form protective layers such as carbon layers, ceramic barrier layers, protective films or insulating coke layers during the combustion process, which greatly improve the anti-drip effect. At the same time, they isolate heat and oxygen transfer and reduce the release of combustible gases. The combined effect of multiple mechanisms significantly improves the flame retardant properties of the material. Furthermore, the flame retardant synergist of the modified polyhedral oligomeric silsesquioxane and its derivatives cooperates with the inorganic flame retardant to synergistically flame retardant, thereby reducing the amount of the flame retardant and improving the flame retardant and crack resistance of the thermoplastic polyolefin material. The thermoplastic polyolefin material provided by the present invention has excellent flame retardant and crack resistance, and can prevent dripping during the combustion process. The modified POSS and its derivatives flame retardant synergist is in the form of a colorless viscous liquid, which has little effect on the performance of the thermoplastic polyolefin material when added to the thermoplastic polyolefin material, and does not require a very high addition amount to obtain a thermoplastic polyolefin material with excellent flame retardancy.
[0061] Further, the benzofuran group includes at least one of a benzofuran group and a dibenzofuran group.
[0062] The carbon-to-hydrogen ratio and carbon content in phenyl are both high, which can slow down the spread of flames during combustion. When the flame is removed, it can quickly extinguish itself, reducing the duration and intensity of combustion. The furan group has a high carbon content and contains oxygen elements that do not participate in combustion. The combination of the two forms a benzofuran group or dibenzofuran group that has both a high carbon-to-hydrogen ratio and a low combustion element. The two work together to form a glass-like protective film or an insulating coke layer during the combustion process. These protective films or coke layers can isolate the air and prevent heat transfer, while reducing the content of combustibles and indirectly promoting carbonization.
[0063] In some embodiments, R2 is a benzofuranyl group.
[0064] In some embodiments, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group, and a perylene ring group.
[0065] The naphthalene ring group, anthracene ring group, phenanthrene ring group, acenaphthene ring group, fluorene ring group and perylene ring group have a relatively high carbon-hydrogen ratio and contain a large amount of carbon elements, which makes it easier to form a glass-like protective film or a heat-insulating coke layer when burned.
[0066] In some embodiments, R2 is a naphthyl ring group.
[0067] Furthermore, the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows:
[0068]
[0069] Furthermore, in the above reaction process, the molar ratio of compound 1 to compound 2 is 2:1.
[0070] The spatial structure of compound 1 polyhedral oligomeric silsesquioxane is relatively large. In the reaction, it is necessary to ensure that compound 2 has a sufficiently small spatial steric hindrance so that it can react with compound 1 to obtain compound 3 modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist. During the reaction, each compound 2 is connected to two compounds 1, that is, the molar ratio of compound 1 to compound 2 is 2:1, which ensures sufficient space for compound 3 and achieves structural stability of compound 3. Compound 2 contains two hydroxyl groups, and the two hydroxyl groups of one compound 2 are respectively combined with one amino group in two compounds 1 to undergo a dehydration reaction to obtain compound 3. The overall reaction requires a single substance, is simple to operate, and is easy to implement.
[0071] In some embodiments, compound 1 is aminopropyl heptaisobutyl caged polysilsesquioxane.
[0072] In some embodiments, compound 1 is aminophenyl heptaisobutyl caged polysilsesquioxane.
[0073] In some embodiments, compound 2 is benzo[B]naphtho[2,3-D]furan-2-hydroxyboronic acid.
[0074] In some embodiments, compound 2 is dibenzofuran-4-boronic acid.
[0075] In some embodiments, the structural formula of compound 3 is:
[0076]
[0077] The following is designated as modified POSS flame retardant synergist 1.
[0078] In some embodiments, the structural formula of compound 3 is:
[0079]
[0080] The following is designated as modified POSS flame retardant synergist 2.
[0081] Furthermore, the preparation method of compound 3 comprises the following steps:
[0082] Compound 1 is dissolved in an organic solvent, and an aqueous solution of compound 2 is added under the action of a catalyst, and the mixture is subjected to a catalytic reaction, and then washed and dried to obtain compound 3;
[0083] Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives;
[0084] The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
[0085] In some embodiments, the catalyst is acetic acid.
[0086] In some embodiments, the solvent is ethanol.
[0087] Furthermore, the raw materials of the thermoplastic polyolefin material include, by weight:
[0088] EVA 20-30 parts,
[0089] POE15-22 parts,
[0090] PE20-30 parts,
[0091] 90-120 parts of inorganic flame retardant,
[0092] 3-8 parts of compatibilizer,
[0093] 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
[0094] Reducing the amount of inorganic flame retardant can further improve the mechanical properties of thermoplastic polyolefin materials.
[0095] Furthermore, the compatibilizer includes at least one of PE grafted maleic anhydride, POE grafted maleic anhydride, PP grafted maleic anhydride, and EMA grafted maleic anhydride.
[0096] The compatibilizer forms a bridge between the base resin and the flame retardant, improving their interfacial compatibility and adhesion, allowing the flame retardant to be more evenly dispersed in the matrix, thereby increasing the filling rate and flame retardant effect and improving the overall performance of the cable. The compatibilizer can also reduce incompatibility problems in the production process, thereby improving the production process and increasing production efficiency.
[0097] Furthermore, the inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide and calcium carbonate.
[0098] It is understood that inorganic flame retardants include but are not limited to magnesium hydroxide, aluminum hydroxide, and calcium carbonate.
[0099] In some embodiments, the inorganic flame retardant is preferably aluminum hydroxide.
[0100] Furthermore, the raw materials of the thermoplastic polyolefin material also include at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, the raw materials, in parts by weight, comprise 0.2-1 part of lubricant, 0.5-2 parts of antioxidant, and 0.2-1 part of light stabilizer.
[0101] In some embodiments, the antioxidant includes, but is not limited to, asymmetric hindered phenol antioxidants, aromatic amine antioxidants, thioether antioxidants, and phosphite antioxidants.
[0102] Hindered phenol antioxidants include, but are not limited to, antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), BHT (2,6-di-tert-butyl-p-cresol), and antioxidant 1076 (β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate);
[0103] Aromatic amine antioxidants include, but are not limited to, diphenylamine, p-phenylenediamine, and dihydroquinoline and their derivatives or polymers, such as: Antioxidant 445 (4,4'-bis(α.α-dimethylbenzyl)diphenylamine);
[0104] Thioether antioxidants include, but are not limited to, DLTP (dilauryl thiodipropionate), DSTDP (distearyl thiodipropionate), and DSTP (octadecyl thiodipropionate);
[0105] Phosphite antioxidants include, but are not limited to, antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 618 (pentaerythritol distearyl diphosphite), and antioxidant 626 (bis[2.4-di-tert-butylphenyl]pentaerythritol diphosphite).
[0106] By adding antioxidants, the anti-oxidation and aging resistance of polymer materials can be improved, and the service life of polymer materials can be extended.
[0107] In some embodiments, the lubricant includes but is not limited to PTFE powder, zinc stearate, magnesium stearate, silicone, calcium stearate or ethylene bis stearamide. By adding the lubricant, it is beneficial to promote a more uniform mixing of various raw materials, improve the fluidity of the polymer resin, reduce the friction coefficient, make the surface of the product smoother, improve the processing efficiency, and improve the transparency and gloss of the plastic.
[0108] In some embodiments, light stabilizers include, but are not limited to, carbon black, zinc oxide, benzotriazoles, and triazines. By adding light stabilizers, multiple mechanisms are used to protect materials, including shielding or reflecting ultraviolet rays, absorbing ultraviolet rays and converting them into heat energy, quenching molecules or groups excited by ultraviolet rays, and capturing free radicals generated by photooxidation and reduction, thereby preventing photooxidation reactions, protecting polymer materials from the effects of light aging, and extending their service life.
[0109] In a second aspect, the present invention provides a method for preparing the above-mentioned thermoplastic polyolefin material, comprising the following steps: uniformly mixing the raw materials, namely EVA, POE, PE, inorganic flame retardant, compatibilizer and modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, extruding and granulating through a mixing extruder to obtain a granular material, namely a thermoplastic polyolefin material.
[0110] Furthermore, the raw material also includes at least one of a lubricant, an antioxidant, and a light stabilizer.
[0111] The content of the present invention is explained below through specific examples and data.
[0112] The information of the raw materials involved in the specific implementation is shown in Table 1:
[0113] Table 1 Information of raw materials of Examples and Comparative Examples
[0114]
[0115]
[0116] The thermoplastic polyurethane elastomer materials obtained in the above examples and comparative examples were injection molded or molded, and flame retardant grade, oxygen index, tensile strength, elongation at break, 110°C heat shock, 130°C heat shock, 150°C heat shock tests were performed. The test standards are as follows:
[0117] (1) Flame retardant grade test
[0118] In accordance with GB / T 5455-2014, the specimens are subjected to vertical burning grade test, the specimens are cut to the specified size and tested under conditions, and key parameters such as burning time limit and residual substances are monitored.
[0119] (2) Whether there is dripping when testing the flame retardancy level
[0120] Whether there is dripping when testing the flame retardancy level is tested according to the UL94 standard, the sample thickness is 3mm, and the test temperature is 23±2℃. The test is carried out using the UL94 vertical combustion test device of Jiangsu Zhengrui Taibang Electronics Co., Ltd.
[0121] (3) Oxygen index
[0122] According to GB / T 2406.2-2009, the sample size is prepared according to the type IV sample. The test is carried out according to method A-top surface ignition method. The test is carried out using the oxygen index tester device of Nanjing Jiangning District Fangshang Analytical Instrument Equipment Factory.
[0123] (4) Tensile strength and elongation at break
[0124] The test was conducted in accordance with Article 9 of GB 1040-2008, the test temperature was 23±2℃, and the tensile test used a standard dumbbell-shaped specimen with a tensile speed of 250mm / min. The tensile strength and elongation at break of 5 specimens were tested using a micro-controlled electronic universal material tensile machine from Dongguan High-speed Railway Testing Co., Ltd., and the results were averaged.
[0125] (5) 110-150℃ thermal shock
[0126] The test was carried out in accordance with Appendix A of GB / T 32129-2015, with a test temperature of 23±2°C and a weight of 2kg. Three samples were tested at each temperature using the thermal shock test device of Hebei Zhongke Beigong Testing Instrument Co., Ltd.
[0127] The test results are shown in Table 3.
[0128] Embodiment 1:
[0129] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain a modified POSS flame retardant synergist 1;
[0130] 30 parts of EVA, 22 parts of POE, 30 parts of PE1, 8 parts of PE grafted maleic anhydride, 10 parts of modified POSS flame retardant synergist 1, 90 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0131] Embodiment 2:
[0132] The preparation method is the same as that of Example 1, except that:
[0133] 20 parts of EVA, 15 parts of POE, 20 parts of PE1, 3 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 130 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0134] Embodiment 3:
[0135] The preparation method is the same as that of Example 1, except that:
[0136] 30 parts of EVA, 22 parts of POE, 30 parts of PE1, 8 parts of PE grafted maleic anhydride, 2 parts of modified POSS flame retardant synergist 1, 90 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0137] Embodiment 4:
[0138] The preparation method is the same as that of Example 1, except that:
[0139] 25 parts of EVA, 18 parts of POE, 25 parts of PE1, 5 parts of PE grafted maleic anhydride, 10 parts of modified POSS flame retardant synergist 1, 130 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0140] Embodiment 5:
[0141] The preparation method is the same as that of Example 1, except that:
[0142] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 130 parts of calcium carbonate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0143] Embodiment 6:
[0144] The preparation method is the same as that of Example 1, except that:
[0145] 30 parts of EVA, 22 parts of POE, 30 parts of PE1, 8 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 120 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0146] Embodiment 7:
[0147] The preparation method is the same as that of Example 1, except that:
[0148] 20 parts of EVA, 15 parts of POE, 20 parts of PE1, 3 parts of PE grafted maleic anhydride, 15 parts of modified POSS flame retardant synergist 1, 120 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0149] Embodiment 8:
[0150] The preparation method is the same as that of Example 1, except that:
[0151] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0152] Embodiment 9:
[0153] The preparation method is the same as that of Example 1, except that:
[0154] 20 parts of EVA, 18 parts of POE, 20 parts of PE2, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 100 parts of calcium carbonate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0155] Embodiment 10:
[0156] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of dibenzofuran-3-boric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain the modified POSS flame retardant synergist 2.
[0157] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 2, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0158] Comparative Example 1:
[0159] The preparation method is the same as that of Example 1, except that:
[0160] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 20 parts of modified POSS flame retardant synergist 1, 92 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0161] Comparative Example 2:
[0162] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 112 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0163] Comparative Example 3:
[0164] The preparation method is the same as that of Example 1, except that:
[0165] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 100 parts of calcium carbonate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0166] Comparative Example 4:
[0167] The preparation method is the same as that of Example 1, except that:
[0168] 20 parts of EVA, 18 parts of POE, 20 parts of PE2, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 1, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0169] Comparative Example 5:
[0170] The preparation method is the same as that of Example 10, except that:
[0171] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of modified POSS flame retardant synergist 2, 100 parts of calcium carbonate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0172] Comparative Example 6:
[0173] The preparation method is the same as that of Example 1, except that:
[0174] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 112 parts of modified POSS flame retardant synergist 1, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0175] Comparative Example 7:
[0176] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 112 parts of calcium carbonate, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0177] Comparative Example 8:
[0178] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant, 0.3 parts of light stabilizer. 80 parts of DuPont 4556 polyether thermoplastic polyester elastomer, 10 parts of benzo[B]naphtho[23-D]furan-2-hydroxyboric acid flame retardant, 5 parts of P series flame retardant, 5 parts of N series flame retardant, 0.5 parts of lubricant, 0.5 parts of antioxidant are mixed evenly, extruded by a twin-screw at 130°C for granulation, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant, halogen-free thermoplastic polyolefin material.
[0179] Comparative Example 9:
[0180] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0181] Comparative Example 10:
[0182] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 6 parts of benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant, 6 parts of aminopropyl heptaisobutyl cage polysilsesquioxane flame retardant, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0183] Comparative Example 11:
[0184] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of methylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain methylboric acid modified POSS flame retardant.
[0185] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of methyl boric acid modified POSS flame retardant, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are evenly mixed, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0186] Comparative Example 12:
[0187] 2 mol of aminopropyl heptaisobutyl caged polysilsesquioxane was dissolved in 100 ml of tetrahydrofuran solution, 0.2 mol of acetic acid catalyst was added to the solution, and 1 mol of phenylboric acid was added under stirring. The reaction was stirred for 2-4 hours, and the reaction was stopped, vacuum rotary evaporation was performed, water was added for washing, and drying was performed to obtain phenylboric acid modified POSS flame retardant.
[0188] 20 parts of EVA, 18 parts of POE, 20 parts of PE1, 5 parts of PE grafted maleic anhydride, 12 parts of phenylboric acid modified POSS flame retardant, 100 parts of aluminum hydroxide, 0.5 parts of lubricant, 0.5 parts of antioxidant and 0.3 parts of light stabilizer are mixed evenly, granulated by twin-screw extrusion at 130°C, and then dried at 80°C to obtain a highly flame-retardant, crack-resistant and halogen-free thermoplastic polyolefin material.
[0189] The components and important preparation variables of Examples 1-10 and Comparative Examples 1-12 are summarized in Table 2. Table 2 Components of Examples 1-9 and Comparative Examples 1-12 of the present invention.
[0190] Table 2 Examples of the present invention and comparative examples
[0191]
[0192]
[0193] According to the provisions of GB / T 1040-2008, GB / T 5455, GB / T 2406.2, GB / T32129 and UL94, the halogen-free thermoplastic polyolefin materials in the above Examples 1-9 and Comparative Examples 1-12 were tested for tensile strength, elongation at break, flame retardancy, oxygen index, 110°C heat shock, 130°C heat shock, 150°C heat shock and dripping during combustion, and the test results were recorded in the following Table 3:
[0194] Table 3 Performance test table of Examples 1-9 of the present invention and Comparative Examples 1-12
[0195]
[0196] According to Table 3, it can be seen that the thermoplastic polyolefin injection molded sheets of Examples 1-10 have high flame retardant properties, and the flame retardant grades all reach V0 level. The V0 level test does not drip, and the oxygen index is >25. It can be seen from Examples 1, 3 and Example 8 that reducing the number of inorganic flame retardants can further improve the mechanical properties of thermoplastic polyolefin injection molded sheets, and improve tensile strength, elongation at break and thermal shock resistance. It can be seen from Example 3, Comparative Example 2 and Example 8 that the number of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists is too low, and the flame retardant properties do not meet the standards; compared with Example 8, the number of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergists in Comparative Example 1 is too high, which will reduce the physical and mechanical properties of the system, resulting in poor plastic deformation ability of the prepared material and easy brittle fracture. It can be seen from Examples 9, 10 and Comparative Examples 2-7 that the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist has a synergistic flame retardant effect with the inorganic flame retardant, which can further improve the flame retardant and anti-drip performance of the thermoplastic polyolefin injection molding sheet. It can be seen from Example 8 and Comparative Example 8 that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist has better anti-drip performance than the benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid flame retardant. It can be seen from Example 8 and Comparative Example 9 that the polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist has better flame retardant and anti-drip performance than the aminopropyl heptaisobutyl caged polysilsesquioxane flame retardant. It can be seen from Example 8 and Comparative Example 10 that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives has better anti-drip performance than the flame retardant mixed with aminopropyl heptaisobutyl caged polysilsesquioxane and benzo[B]naphtho[2,3-D]furan-2-hydroxyboric acid. It can be seen from Example 8 and Comparative Examples 11 and 12 that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives of the present invention has better flame retardant and anti-drip performance than other polyhedral oligomeric silsesquioxane flame retardants containing boric acid modification such as benzofuran groups and polycyclic aromatic groups, thereby indicating that the flame retardant synergist of polyhedral oligomeric silsesquioxane and its derivatives of the present invention has excellent flame retardant and anti-drip performance.
[0197] Therefore, the present invention verifies that the flame retardancy of thermoplastic polyolefin materials is improved by modifying the POSS flame retardant synergist, so that the materials have excellent physical and mechanical properties and excellent combustion and dripping prevention effects, have extremely high industrial value, and can be widely used and promoted.
[0198] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.
Claims
1. A thermoplastic polyolefin material, characterized in that: The raw materials of the thermoplastic polyolefin material include, by weight: EVA 20-30 parts, POE15-22 parts, PE20-30 parts, 90-130 parts of inorganic flame retardant, 3-8 parts of compatibilizer, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist, Wherein, the structure of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is: Wherein, R is a non-reactive group, such as isobutyl, isooctyl, ethyl, cyclohexyl, cyclopentyl, or phenyl, and R1 is n-propyl or phenylene; R2 is a cyclic structure with a carbon-to-hydrogen ratio greater than 1, including at least one of a benzofuran group and a polycyclic aromatic group.
2. The thermoplastic polyolefin material according to claim 1, characterized in that The benzofuran group includes at least one of a benzofuran group and a dibenzofuran group; And / or, the polycyclic aromatic group includes at least one of a naphthalene ring group, an anthracene ring group, a phenanthrene ring group, an acenaphthene ring group, a fluorene ring group and a perylene ring group.
3. The thermoplastic polyolefin material according to claim 1, characterized in that The modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist is prepared by dehydration reaction of compound 1 and compound 2 under the action of a catalyst, and the reaction route is as follows: 。 4. The thermoplastic polyolefin material according to claim 3, characterized in that The molar ratio of compound 1 to compound 2 is 2:
1.
5. The thermoplastic polyolefin material according to claim 3, characterized in that The preparation method of the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist comprises the following steps: Dissolving compound 1 in an organic solvent, adding an aqueous solution of compound 2 under the action of a catalyst, performing a catalytic reaction, and then washing and drying to obtain the modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist; Wherein, the organic solvent includes at least one of alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, alicyclic hydrocarbons, ethers, ketones and diol derivatives; The catalyst includes at least one of an acidic catalyst, a metal catalyst, and a basic catalyst.
6. The thermoplastic polyolefin material according to claim 1, characterized in that The raw materials of the thermoplastic polyolefin material include, by weight: EVA 20-30 parts, POE15-22 parts, PE20-30 parts, 90-120 parts of inorganic flame retardant, 3-8 parts of compatibilizer, 2-15 parts of modified polyhedral oligomeric silsesquioxane and its derivative flame retardant synergist.
7. The thermoplastic polyolefin material according to claim 1, characterized in that The compatibilizer includes at least one of PE grafted maleic anhydride, POE grafted maleic anhydride, PP grafted maleic anhydride, and EMA grafted maleic anhydride.
8. The thermoplastic polyolefin material according to claim 1, characterized in that The inorganic flame retardant includes at least one of magnesium hydroxide, aluminum hydroxide and calcium carbonate.
9. The thermoplastic polyolefin material according to claim 1, characterized in that The raw materials of the thermoplastic polyolefin material also include at least one of a lubricant, an antioxidant, and a light stabilizer; wherein, in terms of weight, the lubricant is 0.2-1 part, the antioxidant is 0.5-2 parts, and the light stabilizer is 0.2-1 part.
10. A method for preparing a thermoplastic polyolefin material as claimed in claim 1, characterized in that: The method comprises the following steps: mixing the raw materials uniformly, extruding and granulating through an extruder, and obtaining granular materials, namely the thermoplastic polyolefin material.
11. The method for preparing a thermoplastic polyolefin material according to claim 10, characterized in that: The raw materials also include at least one of a lubricant, an antioxidant, and a light stabilizer.